Das letras aos números: a produção de estatísticas e ativismos pelos movimentos LGBTI+ - Galbieri, João Otávio (Universidade Federal de São Carlos, 2024)
This dissertation seeks to discuss the production of statistics by LGBTI+ movements, which from the second decade of the 2000s have consolidated the use of numerical narratives as a political strategy. To do so, we interweave the use of different materials and methodologies, such as field data obtained through the use of participant observation in meetings of social movements, recovery of laws that deal with gender and sexuality and qualitative analysis of quantitative data. These data are those found in reports produced by different segments of the LGBTI+ movements, such as the Gay Group of Bahia, between 2011 and 2021, the National Association of Transvestites and Transsexuals, between 2017 and 2023 and the Movement for Advances in Public Policies for Attention to LGBTI+ populations, between 2020 and 2022, an initiative monitored within the scope of the city of São Carlos. The theoretical basis of the research seeks to combine a dialogue between gender and sexuality studies, whose advances allow a conception of the LGBTI+ political subject, with the sociology of quantification, an emerging field in the social sciences, which approach numbers through their social and cultural meanings, not limited to the supposed “neutral” reading of the social reality that they would provide. Our argument is that the "LGBTI+ numbers" direct criticism to the absence of gender identity and sexual orientation in the measurement criteria that underpin the governamental statistics, in addition to evidencing the search for an argument based on statistical language to claim public policies and counteract the absence of administrative-institutional memory in the apparatuses developed for this population.
From letters to numbers: the production of statistics and activisms by LGBTI+ movements
Keywords: População LGBTI+; Estatísticas; Gênero e sexualidade; Movimentos sociais; Quantificação; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS